Analisis Rasio Keuangan Sebagai Alat Menilai Kinerja Keuangan Perusahaan Penerbangan PT. Citilink Indonesia Periode 2019-2022 - Finzeca Mariano; Dwi Anggrani; Khojanah Hasan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to evaluate the financial performance of PT Citilink Indonesia from 2019-2022 using financial ratios. The data used in this research were obtained from the official annual reports published on the PT Citilink Indonesia website. The study focuses on three types of ratios: liquidity ratios, profitability ratios, and solvency ratios. By conducting a quantitative analysis of the financial data, this research assesses how these ratios impact the company's financial performance. The results indicate that while the liquidity ratios of PT Citilink Indonesia are inconsistent, there is an improvement in profitability ratios, suggesting that the company has become more efficient in managing its operations. However, the solvency ratios show an increased financial risk that could affect the company's financial stability in the future. Based on these findings, it is recommended that the company implement more effective debt management strategies to mitigate financial risks and enhance overall performance. These findings provide valuable insights for managers and investors to make more informed decisions about the future financial outlook of PT Citilink Indonesia.